Agricultural Trade : What Matters in the Doha Round? - Laborde, David; Martin, Will (World Bank, Washington, DC, 2014)
This survey concludes that including agriculture in the Doha Agenda negotiations was important both economically and politically, although the political resistance to reform is particularly strong in this sector. While agriculture accounts for less than 10 percent of merchandise trade, high and variable agricultural distortions appear to cause the majority of the cost of distortions to global merchandise trade. Within agriculture, most of the costs appear to arise from trade barriers levied on imports since these barriers tend to be high, variable across time and over products, and are levied by a wide range of countries. The negotiations faced a need for balance between discipline in reducing tariffs and hence creating the market access gains that are central to the negotiations, and flexibility in managing political pressures. While the approach of providing flexibility on a certain percentage of tariff lines is seriously flawed, the proposed Modalities still appear to provide worthwhile market access. Better ways appear to be needed to deal with developing countries' concerns about food price volatility while reducing the collective-action problems resulting from price insulation.